An approach of checking an exit sign system based on navigation graph networks. (October 2020) - Fu, Meiqing; Liu, Rui
Abstract: Exit signs are widely used as an indoor navigation aid, because the information conveyed by exit signs can improve wayfinding efficiency. Existing research mainly focused on signboard design or the placement of several signs in a local space. Nevertheless, to provide effective navigation assistance, exit signs of a building need to work together and form a comprehensive exit sign system to indicate an effective exit route. Few studies treated exit signs of a building as a whole system to assess their design and placement. To fill this gap, this study defines three key characteristics of an effective exit sign system: continuity, consistency, and guiding correctness, proposes the mechanism of the interaction between pedestrians and exit signs on navigation graph networks, and develops a method to check exit sign systems based on navigation graph networks. The proposed method is a workflow that follows the procedure of constructing navigation graph networks using Building Information Modelling (BIM), identifying decision-making nodes, determining the mechanism of the interaction between pedestrians and exit signs, and assessing the effectiveness of exit sign systems in terms of continuity, consistency and guiding correctness. A real case of a three-story educational building is used to validate the feasibility of the proposed method. The results indicate that the proposed method can automatically identify coverage errors, direction conflicts, and guiding direction errors in exit sign systems of buildings. This study sheds substantial light on the design of exit sign systems in buildings and provides an effective tool to help designers and engineers design new exit sign systems and benefit building managers by examining and managing existing exit sign systems.